Pandawa App: Student Guide Application after the Covid-19 Pandemic - Rafdhi, Agis Abhi; Bachtiar, Adam Mukharil; Hayati, Euis Neni; Mega, Raiswati Untsa (International Journal of Informatics, Information System and Computer Engineering (INJIISCOM), 2023)
The purpose of this research is to design a mobile-based application that functions as a pre-lecture socialization platform so that the post-Covid-19 transition period can be maintained and carried out well. The research method used in this research is descriptive analysis with a qualitative approach. We used an object-oriented approach with the System Development Life Cycle Prototyping in the application development process. The results show that the Pandawa application development can provide lecture guidance properly using a digital platform that can be accessed via smartphone. The main concept of this application is to contain procedures or guidelines for implementing face-to-face lectures during the transition period from the Covid-19 pandemic in the New Normal era. In addition, this application also has a feature integrated with the local government for reporting if there are residents who test positive for Covid-19. Therefore, it can be followed up directly and quickly. In the end, this application is present as an information medium to adapt new habits in the world of education, especially at the tertiary level.